The fishery, demographic size structure and oocyte development of dolphinfish, Coryphaena hippurus, in Venezuela and adjacent waters - Arocha, Freddy; Marcano, Luis A.; Larez, Asdrubal; Altuve, Douglas; Alió, Jose (Scientia Marina, 1999)
Dolphinfish, Coryphaena hippurus, is a widely distributed epipelagic species that migrates seasonally in different areas of the oceans. In Venezuelan and adjacent waters it is fished commercially mainly by artisanal fishermen using surface longline and gillnet. Information on effort, location, catch at size, weight and sex determination from 1991 to 1997 was used to determine the seasonality of the demographic structure of dolphinfish off Venezuela. A total of 4876 specimens were measured and sexed from port sampling and observer-covered trips in longline vessels. Oocyte development and spawning season were estimated from samples collected in observer-covered trips on board longline vessels. The seasonality of dolphinfish off Venezuela appears to show two different size groups: one arriving at the end of the first quarter comprised of large mature individuals that will spawn in May, and one arriving at the beginning of the third quarter comprised of smaller specimens that will spawn in October-November. Sex ratio at size was significantly biased towards females in all quarters for smaller specimens (<100 cm FL), while males were predominant in larger size classes (>120 cm FL). Oocyte development revealed an indeterminate spawning pattern, as shown by the asynchronous oocyte development in the material examined. A reproductive strategy is proposed based on the seasonal movement pattern of dolphinfish off Venezuela, which is used to ensure recruitment success due to the prevailing environmental conditions off the Venezuelan coasts.